Effects of simultaneous proton irradiation on the corrosion of commercial alloys in molten fluoride salt. (June 2023) - AlMousa, Nouf; Zhou, Weiyue; Woller, Kevin B.; Short, Michael P.
Abstract: Molten salt fission and fusion reactors hold promise for large-scale, carbon-free power generation, but only if the combined effects of simultaneous irradiation and corrosion on their structural materials can be predicted. Here commercial alloys (SS316L, Incoloy 800 H, Inconel 600) are corroded in molten fluoride salt at 650 ℃ while partially subjected to simultaneous proton irradiation. By comparing corrosion feature depth distributions, it is found that simultaneous proton irradiation accelerates the corrosion of SS316L and Incoloy 800 H, while Inconel 600 does not undergo radiation-accelerated corrosion. Simultaneous proton irradiation accelerates or decelerates corrosion proportional to the ratio of Ni to (Fe+Cr) content. Highlights: Simultaneous proton irradiation/corrosion was studied on commercial alloys in FLiNaK. Radiation enhanced diffusion increases mass fluxes to corrosion features. Proton irradiation affects FLiNaK corrosion proportional to alloy (Fe+Cr) content.